Macroevolutionary patterns in overexpression of tyrosine: An anti-herbivore defence in a speciose tropical tree genus, Inga (Fabaceae) - Coley, Phyllis (2019)
Plant secondary metabolites are a key defence against herbivores, and their evolutionary origin is likely from primary metabolites. Yet for this to occur, an intermediate step of overexpression of primary metabolites would need to confer some advantage to the plant. Here, we examine the evolution of overexpression of the essential amino acid, L-tyrosine and its role as a defence against herbivores. We examined overexpression of tyrosine in 97 species of Inga (Fabaceae), a genus of tropical trees, at five sites throughout the Neotropics. We predicted that tyrosine could act as an anti-herbivore defence because concentrations of 4% tyrosine in artificial diets halved larval growth rates. We also collected insect herbivores to determine if tyrosine and its derivatives influenced host associations. Overexpression of tyrosine was only present in a single lineage comprising 21 species, with concentrations ranging from 5% to 20% of the leaf dry weight. Overexpression was pronounced in expanding but not in mature leaves. Despite laboratory studies showing toxicity of L-tyrosine, Inga species with tyrosine suffered higher levels of herbivory. We therefore hypothesize that overexpression is only favoured in species with less effective secondary metabolites. Some tyrosine-producing species also contained secondary metabolites that are derived from tyrosine: tyrosine-gallates, tyramine-gallates and DOPA-gallates. Elevated levels of transcripts of prephenate dehydrogenase, an enzyme in the tyrosine biosynthetic pathway that is insensitive to negative feedback from tyrosine, were found only in species that overexpress tyrosine or related gallates. Different lineages of herbivores showed contrasting responses to the overexpression of tyrosine and its derived secondary metabolites in their host plants. Synthesis. We propose that overexpression of some primary metabolites can serve as a chemical defence against herbivores, and are most likely to be selected for in species suffering high herbivory due to less effective secondary metabolites. Overexpression may be the first evolutionary step in the transition to the production of more derived secondary metabolites. Presumably, derived compounds would be more effective and less costly than free tyrosine as anti-herbivore defences.